Pengaruh Return on Equity, dan Debt to Equity Ratio terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Farmasi BEI di Masa Pandemi Covid 19 - Wildan Fazrian; Tiar Lina Situngkir (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
During the covid 19 pandemic that hit Indonesia, the pharmaceutical industry sector was one of the sectors most needed to cope with the covid 19 pandemic and during the covid 19 pandemic this sector experienced several improvements, especially in terms of the company's financial condition which can be seen through financial ratios. This study aims to determine, test, and analyze the effect of ROE and DER on firm value (PBV) in pharmaceutical sub-sector companies listed on the Stock Exchange during the covid 19 pandemic. The research method used is descriptive verification, the population used is sub-sector companies. pharmaceutical sector listed on the Stock Exchange with a total sample of 7 out of 10 companies. The sampling technique used is purposive sampling, and the analytical tool used is multiple linear regression with the results of the research that ROE and DER have an effect on firm value (PBV) either partially or simultaneously. Keywords: Return on Equity; Debt to Equity Ratio; Firm Value (PBV)